2006
DOI: 10.1074/jbc.m511683200
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of H-2Db Complexed with a Partial Peptide Epitope Suggests a Major Histocompatibility Complex Class I Assembly Intermediate

Abstract: In the absence of bound peptide ligands, major histocompatibility complex (MHC) class I molecules are unstable. In an attempt to determine the minimum requirement for peptide-dependent MHC class I stabilization, we have used short synthetic peptides derived from the Sendai virus nucleoprotein epitope (residues 324 -332, 1 FAPGNYPAL 9 ) to promote its folding in vitro of H-2D b . We found that H-2D b can be stabilized by the pentapeptide 5 NYPAL 9 , which is equivalent to the C-terminal portion of the optimal n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 31 publications
1
27
0
Order By: Relevance
“…This is consistent with published literature, because the human ␤2m:H-2D b chimeric complex contains more hydrogen bonds between the heavy and light chain and is more stable than its exclusively murine counterpart (22). An x-ray crystal structure has also shown that the H-2D b complex was unexpectedly stabilized by a small pentapeptide fragment, indicating that full occupancy of the peptidebinding groove is a less stringent requirement for stability of this complex (31). Fortunately, variables such as incubation time, temperature, and buffer conditions can provide additional control over the assay, although experience with other HLA variants suggests that by and large the standard peptide exchange conditions sufficiently destabilize MHC molecules (data not show) making the stability of the H-2D b complex a notable exception.…”
Section: Discussionsupporting
confidence: 78%
“…This is consistent with published literature, because the human ␤2m:H-2D b chimeric complex contains more hydrogen bonds between the heavy and light chain and is more stable than its exclusively murine counterpart (22). An x-ray crystal structure has also shown that the H-2D b complex was unexpectedly stabilized by a small pentapeptide fragment, indicating that full occupancy of the peptidebinding groove is a less stringent requirement for stability of this complex (31). Fortunately, variables such as incubation time, temperature, and buffer conditions can provide additional control over the assay, although experience with other HLA variants suggests that by and large the standard peptide exchange conditions sufficiently destabilize MHC molecules (data not show) making the stability of the H-2D b complex a notable exception.…”
Section: Discussionsupporting
confidence: 78%
“…Importantly, experiments in vivo and in vitro have shown that, in the presence of the PLC, peptide loading is iterative, i.e., class I molecules first bind suboptimal peptides (peptides that are too long, too short, or do not have the requisite anchor residues) and gradually exchange them for higher-affinity ones (10,11). The idea that class I molecules can initially fold with such suboptimal peptides is indeed supported by the crystal structures of several class I molecules with octamer or pentamer peptides (12,13).…”
mentioning
confidence: 65%
“…Shorter peptides that correspond to fragments of high-affinity peptides have previously been crystallized in complex with class I molecules (12,13). We therefore hypothesized that short peptides may support the folding of class I molecules but may then be easily removed because of their low affinity for class I.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular dynamic modeling suggests that the region that binds the peptide C terminus is more flexible in the empty state than the corresponding region interacting with the peptide N terminus (31). The empty N-terminal region adopts a "preformed" conformation that is similar to the occupied state (31) and can be largely satisfied by solvents like water in crystal structures (24,26). In contrast, the empty C-terminal region shows much more fluctuation (31), and it has been proposed that the interaction between the F pocket in the C-terminal region, which is near N86, and the C terminus of the bound peptide is most critical for stabilizing MHC class I molecules (26).…”
Section: Discussionmentioning
confidence: 99%